Managing religious congregation’s goods: From professionalism to the service of mercy - Villagrán, Gonzalo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The management of material goods seems incompatible with the practice of compassion, and yet we expect compassion to be present when we deal with religious congregations’ goods. To solve this paradox we should first assure some preconditions when managing religious congregations’ goods: observance of the law and professionalism. We should also add the observance of Canon Law’s prescriptions as a warrant of the ecclesial character of our management. These presuppositions alone lead us to a means-ends paradigm that seems unsatisfactory. Therefore, we should add three criteria in order to introduce compassion in the management of religious congregations’ goods. These criteria are: the mission, the effort to transform economy from the inside and a coherence of life. All this should be put into practice through advisory commissions that gathers different professional and spiritual sensibilities into a prudent discernment.Canon Law; mission; investment; vow of poverty; prudence and logic of gift
Keywords: Canon Law; mission; investment; vow of poverty; prudence and logic of gift